طرق وأساليب إدارة المخاطر في شركات التأمين على الأشخاص –دراسة حالة شركة Axa- - بن شيخ, منال (Université de M'sila, 2018)
تواجه شركات التأمين على الأشخاص مجوعة من المخاطر تهدد استقرارها وتحول دون تحقيقها لأهدافها؛ وبتالي هي ملزمة بإتباع طرق وأساليب تمكنها من إدارة مخاطرها بشكل مناسب. تهدف هذه الدراسة إلى إبراز أهم المخاطر التي تواجه شركات التأمين على الأشخاص وكيفية إدارة هذه المخاطر و توضيح الأساليب المتبعة لمواجهتها. Insurance companies are faced with a range of risks that threaten their stability and prevent them from achieving their objectives; accordingly, they are obliged to follow ways and methods to manage their risks appropriately. This study aims to highlight the most important risks faced by insurance companies and how to manage these risks and to clarify the methods used to address them.
Keywords: إدارة المخاطر؛ التأمين على الأشخاص؛ المخاطر في شركات التأمين.